Factors Affecting the Choice of Islamic Banking by SMEs in Pakistan: Implications for Islamic Banks’ Corporate Governance - Muhammad Bilal (Pakistan Journal of Commerce and Social Sciences, 2020)
Business is an important factor for the development of the economy of any country. Over the last ten years the Government of Pakistan has been playing an important role in promoting the Small and Medium Enterprises (SMEs) and improving their governance standards. It is also true that finance is one of the major elements for businesses and banks are playing an important role to finance the business sector of Pakistan. Therefore, this study has focused on the business community to analyze the factors which influence the adoption of Islamic banking among SMEs in Pakistan. In this regard, 400 business units have been selected as sample size. This research is based on the primary data collected from different areas of the Central Punjab. Several inferential statistics techniques have been used to get results. The study has found significant impact of corporate governance image of the bank, government support, relative advantage, perceived behavior control and subjective norms on the use of Islamic banking among SMEs in Pakistan. The results of this study show a positive impact of Islamic banking to promote the SMEs in Pakistan.